The Face of Russia, Part 2: The Facade of Power - Grigor, Murray (United States, 1998)
The Face of Russia is a personal interpretation of Russia’s cultural history by one of America’s pre-eminent Russian scholars, James H. Billington. Part 2: This program traces the growth of Russian architecture from the Eastern-inspired onion domes and tent roofs of the early wooden churches to the sprawling palaces and vertical spires of secular St. Petersburg. Viewers visit baroque palaces such as Peterhof, with fountains and classical statuary that echo the elegant parks of Italy and France; Rastrelli’s famed Winter Palace in St. Petersburg, and his Summer Palace at nearby Tsarskoe Selo. The program also explores the novel, especially the extraordinary achievement of writer Nikolai Gogol, who saw St. Petersburg as a heartless city—a city for parades rather than for people. The program takes an in-depth look at Gogol’s work of literary genius, Dead Souls, an inspiration to the radicals of the nineteenth century, dissidents of the Soviet period, and filmmakers and theater producers today.
Keywords: Documentary films